Conceptual Framework of a Sustainable Decommissioning Alternative for Offshore Platforms in Malaysia - Wan Abdullah Zawawi, Noor Amila (2012)
The decommissioning activities for shallow-water oil platforms in Malaysia are expected to rise significantly. For many of these 249 oil platforms, their service life is approaching the end. Thus far, only two offshore platforms in Malaysian waters have been decommissioned mainly due to lack of regulatory framework and weak decommissioning plans. The shortage of decommissioning yards provides another major challenge in managing onshore disposal. With a number of options viable in decommissioning our used platforms, a review of these possibilities is timely. The scope of this paper entails the decommissioning methods particularly in the Gulf of Mexico, where conditions are similar to Malaysian waters. Evaluations of methodology as well as sustainability implications are discussed. The usual methods of decommissioning involve any of these options: complete removal, partial removal, reefing or re-using. Employing the aspects of sustainability as a pillar of the study, a conceptual framework of a viable decommissioning scheme is drawn. It was conceptually found that refurbishing the whole of the structure as a livable hub has its own unique potentials. Given the calm conditions of Malaysian waters and the sturdy design of the platforms, the restored structures hold possibilities either as ocean townships or futuristic cities such as a ‘sea-stead’. This novel idea of decommissioning is presented and further discussed in the paper.